Polymorphisms of the receptor for advanced glycation end products and glyoxalase I and long-term outcome in patients with breast cancer - Tesarova, Petra; Zima, Tomas; Kubena, Ales A; Kalousova, Marta (Tumour biology, 2017)
Receptor for advanced glycation end products and glyoxalase I metabolizing advanced glycation end product precursors may play important role in the pathogenesis and progression of cancer. Potential relation between soluble forms of receptor for advanced glycation end products (sRAGE), receptor for advanced glycation end products, glyoxalase I polymorphisms, and long-term outcome (median follow-up of 10.3 years) was studied in 116 patients with breast cancer. Gly82Ser and 2184 A/G RAGE polymorphisms were related to the mortality due to the breast cancer and -419 A/C glyoxalase I polymorphism was related to the overall mortality of the patients suggesting their role not only in the risk of breast cancer but also in the outcome of patients with breast cancer.
Keywords: dospělí; outcome; Kaplan-Meier Estimate; nádory prsu; Receptor for Advanced Glycation End Products; Female; Adult; ženské pohlaví; Kaplanův-Meierův odhad; Lactoylglutathione Lyase; jednonukleotidový polymorfismus; oxidative stress; lidé; Polymorphism, Single Nucleotide; Breast Neoplasms; Aged, 80 and over; laktoylglutathionlyasa; Aged; receptor for advanced glycation end products; polymorphism; lidé středního věku; senioři nad 80 let; senioři; receptor pro konečné produkty pokročilé glykace; Breast cancer; Middle Aged; Humans